Mitochondrial homeostasis: a potential target for delaying renal aging - Yang, Ming; Liu, Chongbin; Jiang, Na; Liu, Yan; Luo, Shilu; Li, Chenrui; Zhao, Hao; Han, Yachun; Chen, Wei; Li, Li; Xiao, Li; Sun, Lin (Frontiers in Pharmacology, 2023)
Mitochondria, which are the energy factories of the cell, participate in many life activities, and the kidney is a high metabolic organ that contains abundant mitochondria. Renal aging is a degenerative process associated with the accumulation of harmful processes. Increasing attention has been given to the role of abnormal mitochondrial homeostasis in renal aging. However, the role of mitochondrial homeostasis in renal aging has not been reviewed in detail. Here, we summarize the current biochemical markers associated with aging and review the changes in renal structure and function during aging. Moreover, we also review in detail the role of mitochondrial homeostasis abnormalities, including mitochondrial function, mitophagy and mitochondria-mediated oxidative stress and inflammation, in renal aging. Finally, we describe some of the current antiaging compounds that target mitochondria and note that maintaining mitochondrial homeostasis is a potential strategy against renal aging.